Insight Into the Mechanism of Exercise Preconditioning in Ischemic Stroke - Zhu, Yuanhan; Sun, Yulin; Hu, Jichao; Pan, Zhuoer (Frontiers in Pharmacology, 2022)
Exercise preconditioning has attracted extensive attention to induce endogenous neuroprotection and has become the hotspot in neurotherapy. The training exercise is given multiple times before cerebral ischemia, effectively inducing ischemic tolerance and alleviating secondary brain damage post-stroke. Compared with other preconditioning methods, the main advantages of exercise include easy clinical operation and being readily accepted by patients. However, the specific mechanism behind exercise preconditioning to ameliorate brain injury is complex. It involves multi-pathway and multi-target regulation, including regulation of inflammatory response, oxidative stress, apoptosis inhibition, and neurogenesis promotion. The current review summarizes the recent studies on the mechanism of neuroprotection induced by exercise, providing the theoretical basis of applying exercise therapy to prevent and treat ischemic stroke. In addition, we highlight the various limitations and future challenges of translational medicine from fundamental study to clinical application.